Improving Quality of Inceptisol Soil from Smallholder Coffee Plantation in Karangploso Area by Utilizing Organic Compost and Animal Manure - Soemarno; Putrideny, Ayesha Ammara; Putri, Rr. Audry Alivianisha; Arifanty, Revina Devi; Pramesti, Gitri Ardia; Ifadah, Nisfi Fariatul (Journal of Coffee and Sustainability, 2024)
Smallholder coffee plantations cover a very large area on inceptisol soil with low productivity; so far, the provision of organic materials in coffee plantations is done by placing it on the surface of the soil so that it is susceptible to loss due to runoff and erosion. This study was conducted by mixing organic materials with topsoil and subsoil to determine their effect on the characteristics of topsoil and subsoil. This study used a Completely Randomized Design (CRD) with 8 treatments and 4 replications. The experimental treatments consisted of P1 (topsoil), P2 (subsoil), P3 (topsoil + Compost); P4 (subsoil + compost); P5 (topsoil + cow manure); P6 (subsoil + cow manure); P7 (topsoil + goat manure); P8 (subsoil + goat manure). The soil was incubated at field capacity conditions for 16 weeks. Soil parameters include: soil pH, soil CEC; soil organic C levels; Ca exchange, Mg exchange, K exchange, and Na exchange. The dose of organic material (cow and goat manure) is 30 tons. ha-1. Providing compost and manure can increase inceptisol soil fertility at the depth of the topsoil and bottom soil (exchangeable K, exchangeable Ca, exchangeable Mg, soil pH, Organic C, and soil CEC levels), this increase is significant compared to the control.